Literature Review on Business Model Innovation: Digital Technology Perspective and Suggestions for Future Research - Yang Li (SAGE Open)
In recent years, there has been exponential growth in research on the impact of digital technologies on business model innovation in enterprises. This paper provides an overview of the literature on business model innovation under the influence of digital technologies. We select 173 peer-reviewed papers and employ a combined quantitative and qualitative research approach to compare the results of different bibliographic analyses, such as citation analysis, co-citation, bibliographic coupling, and keyword co-occurrence, to identify the most influential journals, authors, papers, and three thematic clusters. For each cluster, we analyze the literature and the reasons behind the clustering results. Based on the publication dates of the literature, we identify potential research areas and future directions to address the shortcomings of existing research.